2015
DOI: 10.1016/j.ihj.2015.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Heart-type fatty acid-binding protein (H-FABP) as an early diagnostic biomarker in patients with acute chest pain

Abstract: H-FABP is a highly sensitive biomarker for the early diagnosis of AMI. H-FABP as early marker and cTnI as late marker would be the ideal combination to cover the complete diagnostic window for AMI. Detection of myocardial injury by H-FABP may also be applied in patients with unstable angina. H-FABP can also be used as a marker for early detection of STEMI before the ECG changes become apparent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 17 publications
1
26
0
2
Order By: Relevance
“…Myoglobin, H-FABP, and GP-BB are responsive indicators of cardiomyocyte injuries in the serum. [31] Augmented levels of myoglobin, GP-BB, and H-FABP were found in the serum of DOXtreated cardiotoxic rats in the current study in agreement with the earlier findings, [32,33] whereas, nimbolide treatment decreased H-FABP, myoglobin, and GP-BB levels ( Figure 5).…”
Section: Discussionsupporting
confidence: 92%
“…Myoglobin, H-FABP, and GP-BB are responsive indicators of cardiomyocyte injuries in the serum. [31] Augmented levels of myoglobin, GP-BB, and H-FABP were found in the serum of DOXtreated cardiotoxic rats in the current study in agreement with the earlier findings, [32,33] whereas, nimbolide treatment decreased H-FABP, myoglobin, and GP-BB levels ( Figure 5).…”
Section: Discussionsupporting
confidence: 92%
“…H-FABP is undetectable in normal conditions but is released rapidly from cardiomyocytes into circulating blood after myocardial damage. Previous studies have demonstrated that H-FABP is closely associated with acute coronary syndrome 32 , hypertrophic and dilated cardiomyopathy, heart failure, stroke, obstructive sleep apnea syndrome and pulmonary embolism [14][15][16][17][18][19][20][21] . MI is one of the most serious challenges of contemporary cardiology.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, H-FABP has been used diagnostic marker for acute coronary syndromes 15 . On the other hand, previous studies have demonstrated that serum level of H-FABP is increased in patients with hypertrophic and dilated cardiomyopathy, heart failure, stroke, obstructive sleep apnea syndrome and pulmonary embolism [13][14][15][16][17][18][19][20][21] .…”
mentioning
confidence: 99%
“…e addition of hFABP to hs-cTn has more accuracy and accelerates clinical diagnostic decisions by identifying the patients at low risk for AMI [100,101]. Another study has demonstrated that hFABP has superior sensitivity than cTnI and suggests a combination use of hFABP and cTnI subsequently to diagnose AMI [102].…”
Section: Heart-type Fatty Acid Binding Protein (Hfabp)mentioning
confidence: 99%